The effect of summer pruning on solar radiation conditions in apple orchards - Gonda, I.; Lakatos, L.; Rakonczás, N.; Holb, I. J. (International Journal of Horticultural Science, 2006)
The aim of this study was to measure the solar radiation conditions in the tree and around the tree of pruned (summer pruning) and unpruned trees in an intensive apple orchard. When observing the daily trend of global radiation measured, there was a great reduction at midday hours due to the shadowing effect of the canopy. The reduction reached 70-75% before pruning, while after pruning it was only 20-25%. The relative radiation supply of the canopy space on cloudy days in the morning and late afternoon hours was higher than that of the sunny days. Mean differences between the day and night temperature reduced greatly in the period of intensive fruit colouration in August and September both in the plant stock and outside the plant stock.